PENINGKATAN MOTORIK HALUS ANAK USIA DINI DI ERA REVOLUSI INDUSTRI 4.0 - Kadek Ari Wisudayanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Human resources are the greatest wealth owned by a nation. Quality human resources will certainly improve the welfare of society and advance the country. Education is one of the efforts that can be done to improve quality human resources. Simple games like plasticine, gunning and paper temples can help improve the fine motor skills of children. When your child holds the plasticizer, he will move his hands swiftly, such as squeezing, stretching, rolling and pressing. Choose characters or objects around children that are easily shaped, such as forming a round ball, a triangular cake container, or a rectangular television. The game can be continued with easy tools and materials, such as paper and scissors.Keywords: Fine Motor, Early Childhood, Industrial Revolution 4.0